IMAGE STREAM TRANSFER USING REAL TIME PROTOCOL (International Journal of Engineering and Computer Science, 2017)
This paper describes several existing data link layer protocols that provide real-time capabilities on wired networks, focusing on token-ring and Carrier Sense Multiple Access based networks. Existing modifications to provide better real-time capabilities and performance are also described. Finally the pros and cons regarding the At-Home Anywhere project are discussed. The ability to stream data between web-services is vital for the implementation of complex workflows on the Grid. In this work we investigate various protocols as to their suitability for streaming, taking into consideration issues such as security, reliability and speed over different Grid configurations. To perform these comparisons we have implemented a Server/Client web service that provides a simple API through which Java applications can stream data. As an added bonus, this architecture can be reused by scientific programmers who want to stream data without having to deal with protocol or web service trivialities. Finally, an evaluation of streaming as an alternative to file transfer on Grid environments is offered, based on a number of test case scenarios. Real-time Transport Protocol (RTP) provides a mechanism for sending real-time data such as video and multimedia. Compressing the RTP data packets and coupling the result with Asynchronous Transfer Mode (ATM) technology provides a means to deliver real-time application data over a network